The Effectiveness of Communication on Generasi Pesona Indonesia’s Instagram in Fulfilling Tourism Informationn Needs - Achmad Syah Galang Ramadhan; Sandrina Humaira (Kanal: Jurnal Ilmu Komunikasi, 2023)
The rise of social media platforms has transformed the way individuals access information, with Instagram emerging as a potent medium due to its visual appeal and engaging features. This research, titled "The Effectiveness of Tourism Communication on Generasi Pesona Indonesia’s (GenPI) Instagram in Fulfilling Tourism Information Needs," aims to assess the efficacy of communication on GenPI's Instagram account in meeting the tourism information needs of its followers. The theoretical framework for this research encompasses concepts such as communication, communication effectiveness, new media, Instagram, and information needs. Employing a quantitative approach with a descriptive focus, the study targets the followers of Generasi Pesona Indonesia’s (GenPI) Instagram account(@genpiindonesia), constituting a population of 15,900 individuals. A sample size of 99 respondents is determined using the Taro Yamane formula, selected through purposive sampling. Data is collected through literature review and questionnaires distributed via Google Form. Analysis of the collected data involves single-table and cross-table examinations, and the relationship between variables is assessed using Spearman's Rank Order Correlations formula with SPSS 25 software. The findings indicate that video content on GenPI’s Instagram account effectively fulfills the tourism information needs of followers, providing valuable recommendations and sought-after tourist destinations. Moreover,the research demonstrates a significant relationship between followers' interaction frequency with Generasi Pesona Indonesia (GenPI)'s Instagram account and the extent to which their tourism information needs are satisfied. This study sheds light on the pivotal role of Instagram as a tool for disseminating tourism-related information, exemplified by GenPI's account, in satisfying the informational requirements of its audience.